Surfactant‐Dependent Charge Transfer between Polyoxometalates and Single‐Walled Carbon Nanotubes: A Fluorescence Spectroscopic Study. Issue 2 (28th December 2017) - Hong, Liu; Nakashima, Naotoshi; Li, Yunxing; Jia, Hongbing; Yang, Cheng
Abstract: Hybridizations of redox‐active polyoxometalates (POMs) with single‐walled carbon nanotubes (SWNTs) have been widely investigated for their diverse applications. For the purpose of constructing high‐quality electronic devices, controlling charge transfer within POM/SWNT hybrids is an inevitable issue. As determined by means of fluorescence spectroscopy, electron transfer between SWNTs and a common POM dopant, phosphomolybdic acid (PMo12 ), can be tuned simply by an alteration of nanotube surfactant type from anionic to nonionic. The mechanism is attributed to the influence of surfactant type on the stabilization of the electron donor–acceptor hybrid and effect of surfactant–nanotube interactions. These results will be important to control charge‐transport behavior in nanohybrids consisting of carbon nanotubes. Abstract : Anionic versus nonionic : As studied by fluorescence spectroscopy, charge transfer between a typical polyoxometalate molecule and single‐walled carbon nanotubes (SWNTs) can be tuned simply by changing the nanotube surfactants from those that are anionic to those that are nonionic (see figure).